Effects of Bairui granules (Thesium chinense Turcz.) on patients with the common cold (wind-heat syndrome): a multicenter, randomized, double-blind, double-dummy, controlled trial - Wang, Mingzhe; Ji, Shuyang; Wu, Youqiang; Shen, Guantong; Nie, Weicheng; Ban, Chengjun; Cheng, Miao (Frontiers in Pharmacology, 2025)
BackgroundThe common cold is a prevalent infectious disease affecting the upper respiratory tract worldwide. Wind-heat syndrome is the most common syndrome pattern in traditional Chinese medicine (TCM) associated with the common cold. In this study, we aimed to evaluate the effectiveness and safety of Bairui granules (Thesium chinense Turcz. [Santalaceae; Thesii Herba]) in the treatment of common cold presenting with wind-heat syndrome.MethodsThis multicenter, randomized, double-blind, double-dummy, controlled trial, enrolled adults aged 18–65 years were diagnosed with the common cold (wind-heat syndrome). Patients were randomly assigned in a 2:1 ratio, to receive oral Bairui plus Reyanning granule placebo or Reyanning plus Bairui granule placebo. The primary effectiveness endpoint was the disappearance rate of common cold symptoms after 3 days of treatment. The secondary effectiveness endpoint included the rate of symptom relief over time post-treatment and improvement in TCM syndrome scores on the third day. Safety was also assessed in this study. The trial was registered in the Chinese Clinical Trial Registry (ChiCTR2200063903).ResultsThe main trial population comprised 108 patients in the Bairui group (Bairui + Reyanning granules placebo), and 54 patients in the control group (Reyanning + Bairui granules placebo). Overall, a total of 161 patients completed the trial. The complete symptom resolution rate at day 3 was 41.67% in the Bairui group and 30.19% in the control group (P > 0.05). The median time to fever resolution was 18 h (10, 20) in the Bairui group and 19.5 h (16, 23.5) in the control group (P < 0.05; hazard ratio [HR], 2.00; 95% confidence interval [CI], 1.09–3.69). Although the median time to sore throat resolution was 3 days (IQR: 3, 4) in both the Bairui group and the control group, the overall Kaplan-Meier curves diverged, yielding a HR of 1.83 (95% CI 1.06–3.14; P < 0.05). The incidence of adverse events was comparable between the two groups; all reported events were mild to moderate in severity and reversible.ConclusionBairui Granules significantly improved the resolution rates of fever and sore throat over time compared to Reyanning Granules in patients with the common cold (wind-heat syndrome).